KARAKTER WILAYAH GENANGAN LAKUSTRIN HOLOSEN BERDASARKAN ASPEK SEDIMENTOLOGI DAN STRATIGRAFI ENDAPAN RAWA DAN UNDAK SUNGAI (Studi Kasus Geologi Kuarter Daerah Air Molek dan Sekitarnya, Kab. Singingi dan Kab. Indragiri Hulu, Provinsi Riau) - Suyatman Hidayat; C Basri; Subiyanto Subiyanto; Herman Mulyana; Herman Moechtar (Pusat Survei Geologi, 2009)
This study was based on analyses of sedimentology and stratigraphy of nine sediment samples obtained from shallow boreholes. The boring was done of A - B traverse, southwest â€“ northeast direction around Indragiri river, south of Rengat. The study was focus on river channel and lauctrin deposits under the swamp sediments and river terraces as the resent of penetration of the bore head varies from 3.80 to 9.95 m . Based on the correlation of lateral and vertical variation, the stratigraphic succession can be grouped into two depositional interval i.e. depositional interval I & II. (IP.I & IP II). Vertical changes on the lithologic composition can be related to changes on humidity conditions. It is shown from the changes in the character of the facies between lower and upper lacustrine. Changes in basin centre between lower and upper lacustrine environment, as the result of basement movement caused by tectonic activity, impected to up and down movement of the basin floor.Â Keywords : Quaternary sediments, lacustrine, climate, tectonic